Wholesale electricity price volatility and price bounds: a market comparison - Troy IV, William (2018)
Due to high volatility and frequent price spikes in wholesale electricity market prices, market regulators often impose price bounds on auction and final market prices. This paper applies a model-free intraday-range measure and ARMA-EGARCH(1,1) models to wholesale electricity price data collected from seven markets in the United States and Europe to measure and compare volatilities across the seven markets and the effects of exogenous amendments to price bounds in a subsample of three markets. The paper concludes that the wider a market’s imposed price bounds, the higher the price volatility. Conclusions also suggest that exogenous price bound changes have more significant effects in markets with tighter imposed bounds and that changes made to locational marginal price bounds have greater effects on price behavior than do changes made to energy offer price bounds. Conclusions add to emerging research about the effects of price bounds on electricity price volatility and are relevant for policy makers and market participants concerned with price volatility.